SARS-CoV-2 Spike S1-specific IgG kinetic profiles following mRNA or vector-based vaccination in the general Dutch population show distinct kinetics - Lotus L. van den Hoogen; Marije K. Verheul; Eric R. A. Vos; Cheyenne C. E. van Hagen; Michiel van Boven; Denise Wong; Alienke J. Wijmenga-Monsuur; Gaby Smits; Marjan Kuijer; Debbie van Rooijen; Marjan Bogaard-van Maurik; Ilse Zutt; et al. (Scientific Reports, 2022)
Abstract mRNA- and vector-based vaccines are used at a large scale to prevent COVID-19. We compared Spike S1-specific (S1) IgG antibodies after vaccination with mRNA-based (Comirnaty, Spikevax) or vector-based (Janssen, Vaxzevria) vaccines, using samples from a Dutch nationwide cohort. In adults 18–64 years old (n = 2412), the median vaccination interval between the two doses was 77 days for Vaxzevria (interquartile range, IQR: 69–77), 35 days (28–35) for Comirnaty and 33 days (28–35) for Spikevax. mRNA vaccines induced faster inclines and higher S1 antibodies compared to vector-based vaccines. For all vaccines, one dose resulted in boosting of S1 antibodies in adults with a history of SARS-CoV-2 infection. For Comirnaty, two to four months following the second dose (n = 196), S1 antibodies in adults aged 18–64 years old (436 BAU/mL, IQR: 328–891) were less variable and median concentrations higher compared to those in persons ≥ 80 years old (366, 177–743), but differences were not statistically significant (p > 0.100). Nearly all participants seroconverted following COVID-19 vaccination, including the aging population. These data confirm results from controlled vaccine trials in a general population, including vulnerable groups.